Tinjauan Hukum Islam Tentang Penambahan Takaran Liter pada Jual Beli Komoditi Kopi (Studi Kasus di Desa Buntu Mondong Kecamatan Buntu Batu Kabupaten Enrekang) - Abd. Usama; Rahmat Rahmat; Putra Alam (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to find out an overview of Islamic law regarding the addition of measurements for buying and selling coffee in Buntu Mondong Village, Buntu Batu District, Enrekang Regency. This research uses qualitative methods with the type of field research, using normative juridical, sociological, and case study approaches. The results of the research were found as follows: First, the practice of buying and selling coffee using liters with additional measurements for each liter in Buntu Mondong Village, Buntu Batu District, Enrekang Regency aims to fulfill the measurement of one liter, which is equivalent to 0.65 kg/liter, and this practice has been achieved. generally, applies in society and has been going on for generations, from the past until now. So, this additional measurement cannot be said to be a form of fraud committed by collectors in measuring when buying coffee from farmers. Second, a review of muamalat jurisprudence regarding the practice of buying and selling coffee using liter measurements with additional measurements for each liter in Buntu Mondong Village, Buntu Batu District, Enrekang Regency, which is permissible because it is harmonious and the conditions for buying and selling in the transaction have been fulfilled and there are no prohibitions on buying and selling. that occurred, including that there were no fraudulent practices carried out by muta'āqidain (people who entered into a contract) in the buying and selling transactions.